Approach to The Principal's Leadership in Blusukan - Pestalozi, Donni; Prananosa, Ahmad Gawdy; Erwandi, Rudi; Putra, M Rusni Eka; Marianita, Marianita (Pascasarjana Universitas KH. Abdul Chalim, 2023)
The purpose of this study was to determine the leadership approach of elementary school principals in Lubuklinggau City in blusukan. This study uses a qualitative approach with phenomenological methods. The research subjects consisted of the Principal, the Teacher Council, and the School Staff. Data collection techniques consist of observation, interviews, and documentation. The data analysis technique uses Miles, Huberman, and Saldan’s interactive model, with the flow of the stages of data collection, data reduction, data display, and conclusion drawing and verifying. The results of the study, the school principal's approach to blusukan, is by providing motivation to subordinates, listening to and respecting subordinates' ideas, appreciating the slightest performance produced, and maintaining a family relationship between subordinates and superiors. In conclusion, the school principal establishes a kinship relationship with the school community in carrying out blusukan.